2019
DOI: 10.3762/bjoc.15.202
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining in Trichoderma viride J1-030: discovery and identification of novel sesquiterpene synthase and its products

Abstract: Sesquiterpene synthases in Trichoderma viride have been seldom studied, despite the efficiency of filamentous fungi for terpenoid production. Using the farnesyl diphosphate-overexpressing Saccharomyces cerevisiae platform to produce diverse terpenoids, we herein identified an unknown sesquiterpene synthase from T. viride by genome mining and determined the structure of its corresponding products. One new 5/6 bicyclic sesquiterpene and its esterified derivative were characterised by GC–MS and 1D and 2D NMR spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…47,52 Terpenes are considered the most abundant and chemically diverse class of natural products, with an estimated number of more than 80 000 different compounds. [53][54][55] These highly diverse natural products are derived from the cyclization of polyprenyl diphosphates such as geranyl diphosphate (GPP), farnesyl diphosphate (FPP), geranylgeranyl diphosphate (GGPP) and geranylfarnesyl diphosphate (GFPP) through the action of terpene cyclases (TC). [53][54][55][56] Several terpenoids have been characterized and reported from different Trichoderma spp., however only few of their responsible biosynthetic gene clusters have been experimentally characterized.…”
Section: Fungal Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…47,52 Terpenes are considered the most abundant and chemically diverse class of natural products, with an estimated number of more than 80 000 different compounds. [53][54][55] These highly diverse natural products are derived from the cyclization of polyprenyl diphosphates such as geranyl diphosphate (GPP), farnesyl diphosphate (FPP), geranylgeranyl diphosphate (GGPP) and geranylfarnesyl diphosphate (GFPP) through the action of terpene cyclases (TC). [53][54][55][56] Several terpenoids have been characterized and reported from different Trichoderma spp., however only few of their responsible biosynthetic gene clusters have been experimentally characterized.…”
Section: Fungal Biosynthesismentioning
confidence: 99%
“…[53][54][55] These highly diverse natural products are derived from the cyclization of polyprenyl diphosphates such as geranyl diphosphate (GPP), farnesyl diphosphate (FPP), geranylgeranyl diphosphate (GGPP) and geranylfarnesyl diphosphate (GFPP) through the action of terpene cyclases (TC). [53][54][55][56] Several terpenoids have been characterized and reported from different Trichoderma spp., however only few of their responsible biosynthetic gene clusters have been experimentally characterized. 53,57 Nevertheless the interest in the terpene synthases inventory of different Trichoderma spp.…”
Section: Fungal Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Recently, two groups have independently reported the characterisation of the terpene cyclase responsible for brasilane biosynthesis in Trichoderma spp. 9,10 These reports facilitated the search for the underlying biosynthetic gene clusters in the Hypoxylaceae which led us to investigate the participating tailoring enzymes.…”
mentioning
confidence: 99%
“…Recently, two independent studies found and characterized the terpene cyclases (TaTC6, Tvi09626) responsible for brasilane backbone assembly in Trichoderma spp. 9,10 Using BLASTp homology searches with Tvi09626 as a template, we found a candidate biosynthetic gene cluster (BGC, bra) in the A. truncatum genome containing five genes termed braA-E (Scheme 1). BraA was identified as a terpene cyclase showing 70.9% similarity to Tvi09626, while BraB was annotated as a putative O-glycosyltransferase (O-GT) with homology to the O-GT PaGT involved in fusicoccin biosynthesis in Diaporthe (Phomopsis) amygdali.…”
mentioning
confidence: 99%